Awareness raising workshop for nursing students on the elderly with Alzheimer's disease: contributions to education - Maurício Barros; Claudia Zamberlan; Maria Helena Gehlen; Paloma Horbach da Rosa; Silomar Ilha (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To describe the contribution of an awareness-raising workshop for nursing students on Alzheimer's disease in the context of the elderly/family. Methods: Strategic action-research developed with 15 university students from the sixth to the eighth semester of Nursing at a university institution in the Rio Grande do Sul. The data collected through semi-structured interviews, before and after an awareness-raising workshop on Alzheimer's disease in elderly/family, were subjected to thematic content analysis. Results: Six categories were identified that concern (Mis) perception of Alzheimer's disease in the context of elderly/ family, from the characterization; risk factors; diagnosis; treatment of Alzheimer's disease; from care to family members/caregivers; and care strategies for the elderly with Alzheimer's disease. Conclusion: The awareness-raising workshop enabled the students to broaden and deepen the knowledge on the theme of Alzheimer's disease in the elderly.